Penerapan Prinsip Forward Defence Policy pada Masa Pemerintahan John Howard Studi Kasus: Australia dalam Perang Irak 2003 - , INESYAHANA ASRIFA, Drs. Dafri Agussalim, MA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The emergence of terrorism in the early 20 th century has changing the Australiaâs view of international security. Right away after United State of America launch the campaign Global War on Terror, Australia committed to join in this movement as their effort against terrorism. One of the implementation of the Global War on Terror was the military operation in Iraq War and Australia under John Howardâs leadership decided to become one of the participant in this military operation. John Howardâs decision to deploy troops in Iraq considered as the implementation of forward defence policy.Debate and protest colouring Australia when Howard insisted to apply forward defence by his decision to involved in Iraq war 2003